Professional ethics and engineering - Dill, Kevin; Wells, Scott; Vesilind, P. Aarne; Duke University. Program in Science, Technology and Human Values; National Science Foundation (U.S.). (Durham, NC Duke University, Program in Science, Technology and Human Values, 1999)
The video is designed to enhance professional ethics training for engineering students, it presents scenarios that illustrate common ethical dilemmas
Funded by the National Science Foundation
Director, Kevin Dill ; producer, Scott Wells ; screenplay, P. Aarne Vesilind ; director/photography, Jason Dowdle ; sound recordist, John Santa ; production assistant, Jesse Mesa-Savage ; video post production, Scott Wells
DVD
Keywords: Engineering ethics -- Case studies; Research -- Moral and ethical aspects -- Case studies